2008
DOI: 10.1103/physrevlett.101.144501
|View full text |Cite
|
Sign up to set email alerts
|

Hyperviscosity, Galerkin Truncation, and Bottlenecks in Turbulence

Abstract: It is shown that the use of a high power α of the Laplacian in the dissipative term of hydrodynamical equations leads asymptotically to truncated inviscid conservative dynamics with a finite range of spatial Fourier modes. Those at large wavenumbers thermalize, whereas modes at small wavenumbers obey ordinary viscous dynamics [C. Cichowlas et al. Phys. Rev. Lett. 95, 264502 (2005)]. The energy bottleneck observed for finite α may be interpreted as incomplete thermalization. Artifacts arising from models with α… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
193
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(205 citation statements)
references
References 34 publications
11
193
1
Order By: Relevance
“…But scientists doing numerical simulations of the NSE, say, for engineering, astrophysical or geophysical applications, have also been using hyperviscosity because it is often believed to allow effectively higher Reynolds numbers without the need to increase spatial resolution. Recently, three of us (UF, WP, SSR) and other coauthors have shown that when using a high power α of the Laplacian in the dissipative term for 3D NSE or 1D Burgers, one comes very close to a Galerkin truncation of Euler or inviscid Burgers, respectively [38]. This produces a range of nearly thermalized modes which shows up in large-Reynolds number spectral simulations as a huge bottleneck in the Fourier amplitudes between the inertial range and the far dissipation range.…”
Section: Discussionmentioning
confidence: 99%
“…But scientists doing numerical simulations of the NSE, say, for engineering, astrophysical or geophysical applications, have also been using hyperviscosity because it is often believed to allow effectively higher Reynolds numbers without the need to increase spatial resolution. Recently, three of us (UF, WP, SSR) and other coauthors have shown that when using a high power α of the Laplacian in the dissipative term for 3D NSE or 1D Burgers, one comes very close to a Galerkin truncation of Euler or inviscid Burgers, respectively [38]. This produces a range of nearly thermalized modes which shows up in large-Reynolds number spectral simulations as a huge bottleneck in the Fourier amplitudes between the inertial range and the far dissipation range.…”
Section: Discussionmentioning
confidence: 99%
“…13 for the case α = 200]. Such thermalisation effects in the Galerkin-truncated Euler equation have also attracted a lot of attention [137]; and the link between bottlenecks and thermalisation has been explored in our recent work [134] to which we refer the interested reader. …”
Section: The One Dimensional Burgers Equationmentioning
confidence: 99%
“…It turns out that such a bottleneck does not occur in the conventional Burgers equation. However, it does [134] occur in the hyperviscous one, in which usual Laplacian dissipation operator is replaced by its α th power; this is known as hyperviscosity for α > 1. We show a representative compensated energy spectrum for the case α = 4 in the left panel of Fig.…”
Section: The One Dimensional Burgers Equationmentioning
confidence: 99%
“…These ideas may also be relevant to the relationship between bottleneck effects, statistical mechanics, and effective viscosity caused by eddy noise. 21,22,32 Finally, the breakdown of the correspondence between ideal and dissipative cases is associated with interaction between spectral transfer and the k-space cutoff due to numerical discretization. Understanding this interaction is of importance in assessing the adequacy of resolution in a numerical model.…”
Section: -3mentioning
confidence: 99%
“…The connection between ideal and dissipative dynamics was suggested decades ago 7 and has been of recent interest. 21,22 By t = 1, however, the plots are radically different with small scale coherent structures much less prominent in the ideal run. The correlation coefficient between the current density in ideal and dissipative cases ͑not shown͒ remains very high ͑Ͼ0.98͒ until t Ϸ 0.3, and it declines smoothly toward zero for t Ͼ 1.…”
mentioning
confidence: 99%